2015
DOI: 10.1155/2015/925639
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Vertical Plunging Jet Using a Hybrid Multifluid–VOF Multiphase CFD Solver

Abstract: A novel hybrid multiphase flow solver has been used to conduct simulations of a vertical plunging liquid jet. This solver combines a multifluid methodology with selective interface sharpening to enable simulation of both the initial jet impingement and the long-time entrained bubble plume phenomena. Models are implemented for variable bubble size capturing and dynamic switching of interface sharpened regions to capture transitions between the initially fully segregated flow types into the dispersed bubbly flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 36 publications
(58 reference statements)
1
12
0
Order By: Relevance
“…Figure 11 shows the mean AVF using the CLSVOF method, the LS method, and Equation (14) in the sections of x = 0.12 m, 0.13 m, and 0.14 m. It was found that the AVF peak locations obtained using the CLSVOF method are r = 0.003 m, 0.002 m, 0.002 m at the three different sections, respectively, while it is r = 0.003 m using the LS method at all three sections. The AVF obtained by the CLSVOF method was more consistent with Equation (14) than that of the LS method. Note that the AVF on the centerline using the CLSVOF method is not equal to zero, which is inconsistent with the LS method results.…”
Section: Avfsupporting
confidence: 57%
“…Figure 11 shows the mean AVF using the CLSVOF method, the LS method, and Equation (14) in the sections of x = 0.12 m, 0.13 m, and 0.14 m. It was found that the AVF peak locations obtained using the CLSVOF method are r = 0.003 m, 0.002 m, 0.002 m at the three different sections, respectively, while it is r = 0.003 m using the LS method at all three sections. The AVF obtained by the CLSVOF method was more consistent with Equation (14) than that of the LS method. Note that the AVF on the centerline using the CLSVOF method is not equal to zero, which is inconsistent with the LS method results.…”
Section: Avfsupporting
confidence: 57%
“…Besides more advanced turbulence models in terms of scale-resolving capability, VOF methods should be utilized to capture the phase interface at large accumulated gas cavities, requiring a high spatial resolution. Hybrid approaches, which aim at capturing both, dispersed dilute bubble clusters by a multi-fluid model as well as sharp phase interfaces by a VOF method, have been proposed, e.g., by Wardle and Weller (2013) and Shonibare and Wardle (2015) or Hänsch et al (2012Hänsch et al ( , 2014 and will be adopted in our further studies for the simulation of gas/liquid two-phase flow in centrifugal pumps. It has to be ensured that the dispersed multi-fluid part of the hybrid model converges towards the VOF model either with grid refinement or with an increased gas load of computational cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, by a bubble diameter variation, we have not found a fundamental change of flow pattern in terms of gas cavity accumulation in the diffuser, so that we can conclude that the main conclusion from the horizontal diffuser investigations-i.e., the dominating impact of non-isotropic turbulence modeling-is substantially unaffected by the presumed violation of two-fluid model assumptions. Subsequent studies will focus on the improvement of the two-phase model to combine a dispersed two-fluid with an interphase-resolving (Volume-of-Fluid) method as proposed, e.g., in Hänsch et al (2012), Wardle and Weller (2013), Hänsch et al (2014), and Shonibare and Wardle (2015) to enable two-phase simulations even on fine grids. In the present study, coarse grid results in terms of grid G1 are presented.…”
mentioning
confidence: 99%
“…Hoang et al [23] investigated the influence of the IC coefficient on maximum velocity, interface thickness, and parasitic currents and confirmed that a condition with an IC coefficient of 1 is the best condition to prevent both parasitic currents and numerical diffusion; they also demonstrated the role of cell size in determining the IC coefficient condition. Shonibare and Wardle [24] developed the solver, switching the IC coefficient from 1 to 0 based on the calculated interface curvature of a spherical fluid particle (defined as the inverse of the sphere radius dependent on the bubble and mesh sizes). Anez et al [25] switched the IC coefficient using two criteria: the ratio between minimum interface and actual interface and the grid dependent based on interface resolution quality.…”
Section: Introductionmentioning
confidence: 99%